Optimum choice and placement of concentrating solar power technologies in integrated solar combined cycle systems. (October 2016) - Manente, Giovanni; Rech, Sergio; Lazzaretto, Andrea
Abstract: Concentrating solar power plants projects have been rapidly increasing over the last few years driven by the advances in the solar technology. The operational issues associated with the variable nature of solar energy could be overcome by integrating the solar input into fossil-fuelled power plants. In this paper solar energy is added to the bottoming part of a state-of-the-art three pressure level natural gas combined cycle and parabolic trough, linear Fresnel and solar tower technologies are considered in the search for the optimum integration. Detailed models of the combined cycle and solar field are built in the Thermoflex ® environment to evaluate the performance of different integrated solar combined cycle system configurations. Results show how the placement of solar heat addition affects the heat absorption in the heat recovery steam generator and, in turn, the overall system performance. Unlike solar-only power plants which call for the highest temperature concentrating solar technologies to maximize thermal efficiency, the best integration is obtained here using moderate temperature concentrating solar technologies which enable a significant reduction of the heat transfer irreversibility in the heat recovery steam generator. Accordingly, high solar radiation-to-electricity conversion efficiencies approaching 30% are achieved using well-established solar technologies. Highlights: A selected number of integrated solar combined cycle layouts is analyzed. Parabolic trough, linear Fresnel and solar tower technologies are considered. In the best layout solar heat is used for evaporation of high pressure saturated water. High solar radiation-to-electrical efficiencies approaching 30% are achieved. The exergy analysis explains why some layouts make a better use of solar energy.